Dinamika Kepemimpinan Situasional Dan Dampaknya Pada Efektivitas Strategi Pemasaran: Suatu Penelitian Longitudinal - Fuji Santoso,; Ahmad Wahyudin, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
Using a long-term research approach, the study investigates factors that influence the effectiveness of marketing strategies and the dynamics of situational leadership. We wanted to know how the styles of situational leadership (directive, persuasive, participatory, and delegative) changed over a long time using research designs involving a variety of business organizations from different industries. Marketing performance parameters, such as sales, market share, and consumer response, will be used to calculate the effectiveness variable of a marketing strategy. To obtain qualitative information, in-depth interviews and questionnaires are given to marketing team members and organizational leaders. To combine qualitative and quantitative perspectives, data will be analyzed using longitudinal regression analysis and content analysis. The results of the research are expected to provide a better understanding of how marketing strategies work over time due to situational leadership changes. The practical consequences include guidelines for leaders and managers to adapt their leadership styles to organizational dynamics, while theoretical implications include contributions to leadership literature and marketing strategies. This research is expected to make a significant contribution to our understanding of the complex interaction between situational leadership and the success of marketing strategies in an ever-changing business context.